Holistic development of coal tar lotion by embedding design of experiments (DoE) technique: preclinical investigations. (1st February 2020) - Sharma, Mandeep; Sharma, Gajanand; Singh, Bhupinder; Dhiman, Vandana; Bhadada, Sanjay Kumar; Katare, O.P.
ABSTRACT: Background : The research work endeavors to develop a liquid dosage form of an efficacious antipsoriatic drug, i.e., coal tar, but having problems like variability and patient noncompliance. Methods : The emulsion was prepared by the wet gum method from standardized coal tar. The optimized lotion obtained after sequential experimental designs was characterized for various dosage form and/or coal tar-related properties including efficacy. Results : The formulation deposited more coal tar in the unit area of rat skin than marketed lotions. The efficacy of lotion in psoriasis animal models was more or equivalent to marketed lotions. The formulation showed one compartment body model dermatokinetics, nonirritancy after repeated applications, and stability at room conditions for a year. Conclusion : The formulation with desired attributes was successfully developed.